Discontinuous Matrix Sturm-Liouville Problems - Allahverdiev, Bilender Paşa; Tuna, Hüseyin (Eurasian Mathematical Journal, 2022)
In this paper, we investigate discontinuous matrix Sturm-Liouville problems. We establish an existence and uniqueness result. Next, we introduce the corresponding maximal and minimal operators for this problem and some properties of these operators are investigated. Moreover, we give a criterion under which these operators are self-adjoint. Finally, we give an eigenfunction expansion.